PENGARUH TINGKAT PENGGUNAAN SOSIAL MEDIA TERHADAP MINATBERWIRAUSAHA PADA MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS NEGERISURABAYA - ROSYID KURNIAWAN, YUSRIL (Jurnal Pendidikan Tata Niaga (JPTN), 2013)
The presence of the internet has given in a revolutionary change in the way of everyday life and human activity. Through the internet, everyone can access to the globalized world to obtain various information they need in all her daily needs. Amid rampant internet users from year to year, more businesses that have been pioneered through social media. The purpose of this research is to find out the influence of social media usage levels on entrepreneurial interest in Economic Education students of State University of Surabaya. This research uses a quantitative approach. The population in this research is university students of Economic Education major. The sample are 160 respondents conducted by purposive sampling technique. The data was collected by questionnaires. Statistic descriptive was used to analyze the data. The results showed a significant degree of influence between the use of social media to the entrepreneurial interest with value of tcount as 6,494 and the signification of value are 0,000. The level of use of social media gives influence of 21.1% on the entrepreneurial interest and this includes the low category. Keyword : Social Media , Entrepreneurial Interest